E-029 Symptomatic cerebral vasospasm after trans-sphenoidal resection of pituitary macroadenomas. (16th November 2010) - Puri, A; Zada, G; Zarzour, H; Laws, E; Frerichs, K
Abstract : Introduction: Delayed ischemic events are recognized complications following aneurysmal subarachnoid hemorrhage (SAH). Delayed cerebral vasospasm may also occur following traumatic SAH or craniotomy for skull base tumors. The occurrence of a serious cerebral arterial vasculopathy following trans-sphenoidal surgery for sellar and parasellar lesions is a poorly understood phenomenon and the literature regarding this association is limited to case reports. Consequently, the pathophysiology and optimal management of this condition remains unclear. We present our experience with three patients who developed delayed ischemic events following trans-sphenoidal resection for pituitary macroadenomas complicated by periprocedural peritumoral bleeding. Methods: We report three consecutive patients from the practice of a high volume operator with evidence of peritumoral bleeding, including SAH, on postoperative imaging following trans-sphenoidal resection of pituitary macroadenomas. Two of the three patients required re-operation to evacuate the hematoma in the tumor bed. The patient's records and preoperative and postoperative imaging were retrospectively reviewed. The preoperative status of the peritumoral and distant cerebral arteries was assessed based on the caliber of the flow voids on preoperative MRIs. Results: All three patients with peritumoral bleeding in the setting of trans-sphenoidal surgery for macroadenoma developed delayed ischemic complications. Case No 1 developed global aphasia on postoperative day 5. A head CT revealed bilateral hypodensities in multiple territories and segmental arterial narrowings. A diffuse vasculopathy reminiscent of cerebral vasospasm was found on angiography and treated with intra-arterial verapamil. The patient deteriorated on postoperative day 18 after initial improvement and developed bilateral anterior cerebral artery infarcts. The patient was discharged with bilateral lower extremity weakness. Case No 2 developed behavioral changes on postoperative day 9. A head MRI revealed patchy infarcts in both frontal lobes. Head CT angiography (CTA) revealed diffuse segmental arterial narrowings. Angiography revealed a severe vasculopathy, treated with intra-arterial verapamil. The patient had not returned to her neurologic baseline by the time of discharge. Case No 3 developed a depressed mental status on postoperative day 5 and required re-operation for a postoperative hemorrhage. His neurologic status failed to improve. A head MRI revealed multiple infarcts and CTA showed diffuse segmental arterial narrowings. Angiography confirmed a diffuse severe vasculopathy which was treated with intra-arterial verapamil. The patient died on postoperative day 12 from multiple strokes. The timing and pattern of the vasculopathy in these cases resembles that of delayed cerebral vasospasm following aneurysmal SAH. Based on the limited analysis of the preoperative imaging, this vasculopathy did not represent a pre-existing condition of these vessels such as 'stretching' around the tumor capsule. Conclusions: Perioperative peritumoral bleeding following trans-sphenoidal surgery for macroadenoma can be associated with severe delayed ischemic complications due to delayed vasospasm. The unique anatomical relationships of the tumor capsule to the major arteries of the circle of Willis may render these vessels more vulnerable to vasospasm. The associated morbidity and mortality was severe. A patient with evidence of peritumoral hemorrhage should be expected to be at high risk for delayed vasospasm and managed accordingly with early cerebrovascular surveillance and intervention similar to patients with aneurysmal SAH.